Faktor-Faktor yang Berhubungan dengan Kelengkapan Imunisasi Dasar Pada Bayi di Wilayah Kerja Puskesmas Duren Seribu Kota Depok Tahun 2022 - Muqsith, Shelly Fadhilah; Andriyani; Munaya Fauziah; Ernyasih (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
Immunization is one of the efforts made by the government to reduce mortality in infants and toddlers. Immunization is adequate primary prevention to prevent infectious diseases that can be prevented through immunization. According to the Ministry of Health, the number of complete basic immunization coverage in 2020 will be the lowest during 2011-2020. To determine the factors in mothers related to the completeness of primary immunization for infants in the working area of the Duren Seribu Health Center, Depok City, in 2022. This study was an analytical research type with a cross-sectional design. This study uses purposive sampling with a total sample of 92 respondents. Data were collected using a questionnaire, and the data collected were analyzed using the chi-square test. Statistical results showed that 84.8% of mothers provided complete primary immunization. The results of the bivariate test with = 0.05 were found; there is a significant relationship between the mother's knowledge (p-value = 0.002), a number of children (p-value = 0.016), availability of health facilities (p-value = 0.003) and family support (p-value = 0.000) with the completeness of primary immunization, there is no relationship between maternal education (p-value = 0.705), mother's employment status (p-value = 1,000), family income (p-value = 0.949), affordability to health services (p-value = 0.729) and the role of health workers (p-value = 0.176) with basic immunizations. Factors related to completeness of immunization in infants are the mother's knowledge (p-value = 0.002), the number of children (p-value = 0.016), availability of health facilities (p-value = 0.003), and family support (p-value = 0.000). It is hoped that mothers will be more active in seeking information about basic immunizations that should be given to babies.